Integrated management of cardiovascular risk : [report of a WHO meeting : Geneva, 9-12 July 2002] (WHO, 2002)
The health outcomes of millions of individuals with cardiovascular risk factors, who are vulnerable to strokes and heart attacks, can only be improved through an integrated approach that addresses overall cardiovascular risk. There are many barriers to implementing such an approach, particularly in low-resource settings. The WHO CVD-Risk Management package has been developed in order to facilitate integrated care of cardiovascular risk despite these barriers. It informs policy-makers of the need and feasibility of managing cardiovascular risk in less well-resourced settings and enables cardiovascular risk management (in settings faced with low resources) through affordable approaches and rational resource allocation. It also facilitates a paradigm shift from single risk factor management to comprehensive cardiovascular risk management through simplified clinical pathways and promotes evidence-based non-pharmacological treatment of cardiovascular risk and operationalization of clinical prevention aided by counselling protocols. Finally, it promotes the use of cost-effective generic drugs for management of cardiovascular risk and empowers patients and their families to cope with a long-term illness .
Keywords: rizikové faktory; Disease Management; kardiovaskulární nemoci; rozvojové země; diagnostika; Risk Factors; veřejné zdravotnictví; hypertenze; Hypertension; LÉKAŘSTVÍ ZALOŽENÉ NA FAKTECH; Cardiovascular Diseases; angiologie; kardiologie; management nemoci; Developing Countries